Finance growth nexus: evidence from a panel of MENA countries - AL-MalkawI, Husam-Aldin Nizar; Abdullah, Naziruddin (EuroJournals Publishing, 2011)
The finance-growth relationship has been extensively researched in recent decades.To date, however, there is no consensus among researchers on this issue. The current paper aims at shedding some lights on the relationship between financial development and economic growth focusing on data gathered from the Middle East and North Africa(MENA) region. Specifically, the study uses a panel dataset of thirteen MENA countries for the period 1985-2005. The estimation method is based on pooled OLS regression with robust standard errors, fixed effects and random effects models. To deal with potential endogeneity problems we run fixed and random effects models with instrumental variables. The result suggests that there is a positive relationship between financial development and economic growth. The study also documents that inflation and government expenditure have negative impact on economic growth for those selected MENA countries. The paper ends with some policy implications and potential limitations.